Gambaran Pemenuhan Kebutuhan Spiritual Lansia Menjelang Ajal Dari Prespektif Pelaku Rawat Di Panti Pelayanan Sosial Lanjut Usia (PPSLU) Kendal - Setianingsih Setianingsih; Lestari Eko Darwati; Rina Anggraeni; Alvin Maulana (Jurnal Ventilator, 2023)
The elderly who are cared for in an elderly care home require spiritual needs to be met, and there are times when the elderly use the resources available either from the family, people who are religious experts either in the hospital or others in the elderly community. Therefore, the fulfillment of the spiritual needs of the elderly must be done so that the elderly on the eve of death can die in a calm and peaceful state. The purpose of this study was to determine the description of the fulfillment of spiritual needs in the elderly near death from the perspective of the caregiver at the Kendal elderly Social Service Center (PPSLU). This study uses descriptive survey research design. The sample in this study amounted to 36 respondents. Sampling using total sampling. The results showed that the majority of hospitalists were aged based on a median value of 41 years, male gender as much as 53%, high school education as much as 53%, have long worked >3 years as much as 89% and meet the fulfillment of spiritual needs in the elderly near death as much as 44%. The caregiver is only limited to fulfilling the spiritual needs of meaning, purpose and hope in life but in the spiritual needs of relationship with God; spiritual practice has not been fulfilled. This is because the caregiver's understanding of spiritual needs is only limited to religion or belief.